German stock returns: The dance with the dollar - Horst Entorf; Gösta Jamin (University of Würzburg, Department of Economics, 2000)
In this paper, we try to shed some light on the association between the stock returns of German DAX corporations and movements of the U.S. Dollar. The link turns out to be rather unstable, but it depends significantly on direction and magnitude of foreign trade, and on the existing level of the DM/ Dollar exchange rate. This conclusion is based on exchange-rate-exposure and APT-modelling, as well as on panel data on the performance of 28 German DAX corporations, inclusion of macroeconomic risk factors, data on export and import involvement, and on econometric panel, GLS, SUR and cointegration techniques.
Keywords: 330